Reduced up-regulation of the nitric oxide pathway and impaired endothelial and smooth muscle functions in the female type 2 diabetic goto-kakizaki rat heart. Issue 1 (December 2017) - Desrois, Martine; Lan, Carole; Movassat, Jamileh; Bernard, Monique
Abstract Background Type 2 diabetes is associated with greater relative risk of cardiovascular diseases in women than in men, which is not well understood. Consequently, we have investigated if male and female displayed differences in cardiac function, energy metabolism, and endothelial function which could contribute to increased cardiovascular complications in type 2 diabetic female. Methods Male and female Control and type 2 diabetic Goto-Kakizaki (GK) isolated rat hearts were perfused during 28 min with a physiological buffer before freeze-clamping for biochemical assays. High energy phosphate compounds and intracellular pH were followed using31 P magnetic resonance spectroscopy with simultaneous measurement of contractile function. Nitric oxide (NO) pathway and endothelium-dependent and independent vasodilatations were measured as indexes of endothelial function. Results were analyzed via two-way ANOVA, p <  0.05 was considered as statistically significant. Results Myocardial function was impaired in male and female diabetic versus Control groups (p <  0.05) without modification of energy metabolism. Coronary flow was decreased in both diabetic versus Control groups but to a higher extent in female GK versus male GK rat hearts (p <  0.05). NO production was up-regulated in diabetic groups but to a less extent in female GK rat hearts (p <  0.05). Endothelium-dependent and independent vasodilatations were impaired in female GK rat compared with male GK (p <  0.05) and female Control (p <  0.05) rat hearts. Conclusions We reported here an endothelial damage characterized by a reduced up-regulation of the NO pathway and impaired endothelial and smooth muscle functions, and coronary flow rates in the female GK rat hearts while energy metabolism was normal. Whether these results are related to the higher risk of cardiovascular complications among type 2 diabetic female needs to be further elicited in the future.